PENGARUH LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA: STUDI KEPUSTAKAAN - Laborahima, M.Jibril; Hinggil Permana; Agus susilo saefullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines how the school environment influences students' learning motivation through a structured library review. Fifteen verified references published between 1998 and 2024 were selected from peer-reviewed journals and an OECD report. The literature was classified into physical, social, academic, safety-discipline, and institutional dimensions and analyzed descriptively. The findings indicate that a positive school environment is consistently associated with stronger interest, persistence, participation, belonging, and academic engagement. Comfortable learning spaces reduce distraction; supportive teacher-student and peer relationships strengthen psychological safety and relatedness; clear expectations, fair discipline, informative feedback, and autonomy-supportive instruction reinforce competence and the perceived value of learning tasks. These dimensions operate interactively rather than independently. Therefore, schools should evaluate facilities, relationships, instructional practices, safety, and student voice as one integrated motivational system. Because much of the evidence is correlational, the term influence should be interpreted as a theoretically supported relationship rather than a single causal estimate.